1D/2D Nanomaterials Synergistic, Compressible, and Response Rapidly 3D Graphene Aerogel for Piezoresistive Sensor. (12th July 2020) - Cao, Xueyuan; Zhang, Juan; Chen, Siwei; Varley, Russell John; Pan, Kai
Abstract: Graphene‐based aerogels have been widely studied for their high porosity, good compressibility, and electrical conductivity as piezoresistive sensors. However, the fabrication of graphene aerogel sensors with good mechanical properties and excellent sensing properties simultaneously remains a challenge. Therefore, in this study, a novel nanofiber reinforced graphene aerogel (aPANF/GA) which has a 3D interconnected hierarchical microstructure with surface‐treated PAN nanofiber as a support scaffold throughout the entire graphene network is designed. This 3D interconnected microporous aPANF/GA aerogel combines an excellent compressive stress of 43.50 kPa and a high piezoresistive sensitivity of 28.62 kPa −1 as well as a wide range (0–14 kPa) linear sensitivity. When aPANF/GA is used as a piezoresistive sensor, the compression resilience is excellent, the response time is fast at about 37 ms at 3 Pa, and the structural stability and sensing durability are good after 2600 cycles. Indeed, the current signal value is 91.57% of the initial signal value at 20% compressive strain. Furthermore, the assembled sensors can monitor the real time movement of throat, wrist pulse, fingers, wrist, and knee joints of the human body at good sensitivity. These excellent features enable potential applications in health detection. Abstract : In this study, electrospinning nanofibers are pretreated as reinforcement materials to prepare nanofiber‐reinforced graphene aerogels. Benefitting from the introduction of nanofibers, the 1D/2D materials hybrid aerogels exhibit a unique hierarchical structure consisting of a layered structure, pore structure, and nanofibers, which provide excellent mechanical properties and piezoresistive performance for nanofiber‐reinforced graphene aerogels.